Conflict Resolution Efforts Through The Implementation Of Inclusive Development In The New National Capital Region - Andi Muhammad Ilham Rusali Masdar; Puguh Santoso; Agus Adriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The relocation of the national capital to east kalimantan requires various preparations. one of them is the need for strategies from the government in various anticipation of potential conflicts that can occur in the new capital region. the relocation of the national capital triggers the creation of friction due to development between migrants and local people who have long lived. There are potential conflicts that can come from various aspects such as social, economic, cultural, political, and this will certainly affect Indonesia's national resilience in preparing for the future of the new IKN. The results of this study are in the form of potential socio-economic conflicts that are packaged in conflict sources in the form of structural conflicts, conflicts of interest, conflicts of values, psychological social conflicts, and also data conflicts in the form of the environment, customs, and livelihoods of the people in IKN. Based on this research, the concept of inclusive development can be applied by the central government by paying attention to three components, namely social structure, culture, and social processes. There are several ways that can be done as conflict resolution actions, one of which is with an inclusive development approach which certainly requires the involvement of all levels of society in the development process. The relocation of the national capital to east kalimantan requires various preparations. one of them is the need for strategies from the government in various anticipation of potential conflicts that can occur in the new capital region. the relocation of the national capital triggers the creation of friction due to development between migrants and local people who have long lived. There are potential conflicts that can come from various aspects such as social, economic, cultural, political, and this will certainly affect Indonesia's national resilience in preparing for the future of the new IKN. The results of this study are in the form of potential socio-economic conflicts that are packaged in conflict sources in the form of structural conflicts, conflicts of interest, conflicts of values, psychological social conflicts, and also data conflicts in the form of the environment, customs, and livelihoods of the people in IKN. Based on this research, the concept of inclusive development can be applied by the central government by paying attention to three components, namely social structure, culture, and social processes. There are several ways that can be done as conflict resolution actions, one of which is with an inclusive development approach which certainly requires the involvement of all levels of society in the development process.